2003
DOI: 10.1186/rr196
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain and physiological adaptation of the rat diaphragm in elastase-induced emphysema

Abstract: Background: Several physiological adaptations occur in the respiratory muscles in rodent models of elastase-induced emphysema. Although the contractile properties of the diaphragm are altered in a way that suggests expression of slower isoforms of myosin heavy chain (MHC), it has been difficult to demonstrate a shift in MHCs in an animal model that corresponds to the shift toward slower MHCs seen in human emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 52 publications
4
18
0
1
Order By: Relevance
“…Changes in type IIB fibers are sometimes present, but these represent 5-10% of the total fibers in the rodent diaphragm and probably are nonexistent in the human diaphragm. The lack of consistent shifts in fiber populations is also consistent with one study by Kim et al (36) that showed only minor changes in the proportions of MHC isoforms in the rat emphysema model.…”
Section: Changes In Fiber Phenotype and Sizesupporting
confidence: 79%
See 4 more Smart Citations
“…Changes in type IIB fibers are sometimes present, but these represent 5-10% of the total fibers in the rodent diaphragm and probably are nonexistent in the human diaphragm. The lack of consistent shifts in fiber populations is also consistent with one study by Kim et al (36) that showed only minor changes in the proportions of MHC isoforms in the rat emphysema model.…”
Section: Changes In Fiber Phenotype and Sizesupporting
confidence: 79%
“…In animal models of elastase-induced emphysema, after periods of 6 mo or more, most studies have found that changes in fiber distributions between type I, IIA, IIB, and IIX are modest and quite variable (22,31,32,36,43,44,49,52,85), as summarized in Table 1. None have found a significant elevation in the proportion of type I fibers, and there has been only one report of significant increases in the proportion of type IIA fibers (49), with an accompanying reduction in IIX fibers.…”
Section: Changes In Fiber Phenotype and Sizementioning
confidence: 99%
See 3 more Smart Citations